Oxygen availability and skeletal muscle oxidative capacity in patients with peripheral artery disease: implications from in vivo and in vitro assessments - Hart, Corey R.; Layec, Gwenael; Trinity, Joel D.; Le Fur, Yann; Gifford, Jayson R.; Clifton, Heather L.; Richardson, Russell S. (American journal of physiology. Heart and circulatory physiology, 2018)
Evidence suggests that the peak skeletal muscle mitochondrial ATP synthesis rate ( V max ) in patients with peripheral artery disease (PAD) may be attenuated due to disease-related impairments in O 2 supply. However, in vitro assessments suggest intrinsic deficits in mitochondrial respiration despite ample O 2 availability. To address this conundrum, Doppler ultrasound, near-infrared spectroscopy, phosphorus magnetic resonance spectroscopy, and high-resolution respirometry were combined to assess convective O 2 delivery, tissue oxygenation, V max , and skeletal muscle mitochondrial capacity (complex I + II, state 3 respiration), respectively, in the gastrocnemius muscle of 10 patients with early stage PAD and 11 physical activity-matched healthy control (HC) subjects. All participants were studied in free-flow control conditions (FF) and with reactive hyperemia (RH) induced by a period of brief ischemia during the last 30 s of submaximal plantar flexion exercise. Patients with PAD repeated the FF and RH trials under hyperoxic conditions (FF + 100% O 2 and RH + 100% O 2 ). Compared with HC subjects, patients with PAD exhibited attenuated O 2 delivery at the same absolute work rate and attenuated tissue reoxygenation and V max after relative intensity-matched exercise. Compared with the FF condition, only RH + 100% O 2 significantly increased convective O 2 delivery (~44%), tissue reoxygenation (~54%), and V max (~60%) in patients with PAD ( P < 0.05), such that V max was now not different from HC subjects. Furthermore, there was no evidence of an intrinsic mitochondrial deficit in PAD, as assessed in vitro with adequate O 2 . Thus, in combination, this comprehensive in vivo and in vitro investigation implicates O 2 supply as the predominant factor limiting mitochondrial oxidative capacity in early stage PAD. NEW & NOTEWORTHY Currently, there is little accord as to the role of O 2 availability and mitochondrial function in the skeletal muscle dysfunction associated with peripheral artery disease. This is the first study to comprehensively use both in vivo and in vitro approaches to document that the skeletal muscle dysfunction associated with early stage peripheral artery disease is predominantly a consequence of limited O 2 supply and not the impact of an intrinsic mitochondrial defect in this pathology.